PENGEMBANGAN MEDIA PUBLIKASI MUSEUM SISA HARTAKU - Anung Rachman; Nerfita Primadewi (Institut Seni Indonesia Surakarta, 2016)
The aim of the Community Services Group Program is to increase the number of visitspenginformasian through Sisa Hartaku and marketing globally Museum. Forms of developmentactivities carried out in the form of media publicity in the form of websites. Training provided tosupport these activities in the form of workshops pengoperasiaan camera, online article writingworkshops, workshop development and maintenance of websites. Subject training on this programare the members of the group manager of the museum and gift shop. The method used in thetraining is through discussion and practice. Through this training is expected to provide a solutionto the problem petrified low levels of traffic in Sisa Hartaku Museum. The training lasted for eightsessions, with training materials through the planning, preparation, manufacture, testing andmaintenance. Form of training starts from the discussion of the expected material relatedpublications by program partners. Mount Merapi and Wedhus Gembel (Cloud Heat) selected asmanifested in the form of brand and logo. Brand is an important guide in this publication mediadevelopment program. Partners are expected to recognize the special characteristics of businessand then used as an attraction for the public. So that potential visitors would come to the rest of mypossessions Museum directly after getting information via the website www.sisahartaku.com. Trainingresults indicate that the importance of website ownership for driving the business at this time.Website created quite informative and was able to increase the number of visitors to the Museum.Approximately thirty percent increase in the number of visits made media than pre- publicationcan be achieved. This has an impact on increasing the number manually souvenir product salesamounted to one hundred percent, but it has not happened yet online transactions during theexecution of programs.Key words : website, museum, Merapi, Wedus Gembel.